1995
DOI: 10.1523/jneurosci.15-07-04786.1995
|View full text |Cite
|
Sign up to set email alerts
|

Changes in c-fos mRNA expression in rat brain during odor discrimination learning: differential involvement of hippocampal subfields CA1 and CA3

Abstract: Levels of c-fos mRNA were measured with in situ hybridization to test for behaviorally dependent changes in neuronal activity in three subdivisions of hippocampus and in components of the olfactory and visual systems. In rats that performed a well-learned nose-poke response for water reward, c-fos mRNA levels were broadly increased, relative to values in home cage-control rats, in visual cortex, superior colliculus, olfactory bulb, and, to comparable levels, regions CA3 and CA1 of hippocampus; hybridization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 6 publications
8
54
0
Order By: Relevance
“…We also observed Arc mRNA clusters in DG (Fig. 4A) that resemble the c-fos mRNA clusters observed after performance on the odor discrimination task (Hess et al, 1995).…”
Section: Dentate Gyrussupporting
confidence: 70%
“…We also observed Arc mRNA clusters in DG (Fig. 4A) that resemble the c-fos mRNA clusters observed after performance on the odor discrimination task (Hess et al, 1995).…”
Section: Dentate Gyrussupporting
confidence: 70%
“…Previous studies have found that hippocampal cellular discharge activity is influenced by a complex interaction of associative and contextual stimuli in the environmental (e.g., Foster et al, 1986Foster et al, , 1989Eichenbaum et al, 1989;Otto and Eichenbaum, 1992;Melia et al, 1994;Hess et al, 1995). The activity observed in these animals may be because of the processing of environmental stimuli, generalized effects of stress, or even motor activity.…”
Section: Discussionmentioning
confidence: 97%
“…The immediate early gene c-fos and its protein product Fos are considered markers of cellular activity (Dragunow and Faull, 1989;Sheng and Greenberg, 1990;Morgan and Curran, 1991;Sagar and Sharp, 1993). In the visual cortex, brief exposure to light induces a larger increase in Fos expression during the sensitive period (Rosen et al, 1992;Beaver et al, 1993;Mower, 1994); in the adult rat hippocampus, expression is induced by a number of environmental stimulations (Tischmeyer et al, 1990;Handa et al, 1993;Melia et al, 1994;Hess et al, 1995; Figure 1. Performance on the Y-maze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested the importance of the CA3 region of the hippocampus in memory formation (Hess et al 1995;Gall et al 1998;Zhao et al 2000). For instance, Gall et al (1998) have demonstrated in twoodor discrimination learning that preferential activation of the CA3 region is uniquely associated with initial learning of an odor pair, whereas predominant activation of the CA1 occurred on exploration of a novel field and with overtrained animals' responding to odors.…”
Section: Discussionmentioning
confidence: 99%